PELAKSANAAN PERKAWINAN BEDA AGAMA DENGAN PENETAPAN PENGADILAN NEGERI DITINJAU DARI UNDANG-UNDANG NO 1 TAHUN 1974 TENTANG PERKAWINAN DAN UNDANG-UNDANG NO 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN (Analisis 3 (tiga) Penetapan Pengadilan Negeri di Indo - Rurin Tiopani Tambun; Hasim Purba; Utary Maharani Barus; Yefrizawaty Yefrizawaty (Universitas Sumatera Utara, 2018)
ABSTRACT Marriage is an event which is important in human life. Marriage is also regarded as something sacred because every religion always connects the rules of marriage with religious principles. Along with the development of the era, the phenomenon of different religious marriages are not a new thing in Indonesia. The methods used in this thesis is normative juridical research. The results show that the implementation of different religious marriages with the Determination of State Court according to The Enactment of Law No. 1 of 1974 about Marriage is law does not recognize the different religious marriages. While the implementation of different religious marriages with the determination of the State Court according to The Enactment of Law No 23 of 2006 about Population Administration is to apply the establishment of marriage of different religions to the registrar of State Court, then will be examined by the judge in court, and then the Judge will order the Department of Population and Civil Registry to record the marriage of the different religions. Consideration of the judges in giving the different religious marriage license are using Article 35 of Enactment of Law No. 23 of 2006 about Population Administration, MARI’s determination No. 1400K / Pdt / 1986 dated January 20, 1989, Article 27 of the 1945 Constitution, and Article 10 paragraph (1) and (2) of Enactment of Law No. 39 of 1999 about Human Rights. The legal consequences of the determination of the State Court is marriage of the different religions is a invalid marriage. Because the marriage of different religions has violated the provisions of Article 2 paragraph (1) regulating the validity of marriage and Article 8 which regulates the marriage ban in The Enactment of Law No. 1 of 1974 about Marriage. Children born in different religious marriage will be an illegitimate children, because they are inconsistent with the contents of Article 42 of the Marriage Law. Keywords: Marriage, Different Religions, Legal Considerations